If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 + w = -4w + 2 Reorder the terms: -18 + w = 2 + -4w Solving -18 + w = 2 + -4w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '4w' to each side of the equation. -18 + w + 4w = 2 + -4w + 4w Combine like terms: w + 4w = 5w -18 + 5w = 2 + -4w + 4w Combine like terms: -4w + 4w = 0 -18 + 5w = 2 + 0 -18 + 5w = 2 Add '18' to each side of the equation. -18 + 18 + 5w = 2 + 18 Combine like terms: -18 + 18 = 0 0 + 5w = 2 + 18 5w = 2 + 18 Combine like terms: 2 + 18 = 20 5w = 20 Divide each side by '5'. w = 4 Simplifying w = 4
| x+40.44=30 | | (4x-7)(3x+4)= | | (3)3x-4+9=6 | | 32+b=42 | | -220x+7208=0 | | -14=2.5(9-2b) | | .25x-1.5y=6 | | -30-5n=2(-6n+6) | | n+14=73 | | -9x+3=4x+10 | | 80x+320=0 | | (11x+2)(8x+7)= | | 80x+320=-220x+7208 | | -6v+2=-6v-4 | | 60+5y=80 | | -15+7x=33-4x | | 3x^2-6=-3 | | 4x+4(x+2)=48 | | Inx+In(x-6)=5 | | x^2-25x-9350=0 | | 30-5x=-6-24 | | 24+17+b=56 | | x^2+3x=1.5 | | 4(x-4)+3=2x-1 | | x^2+y^2=13 | | -1fith*y=10 | | (x+2)(x-2)=2 | | 5m+2(1m+1)=23 | | (x+2)(x-2)=10 | | (x+2)(x-2)=4 | | (x+2)(x-2)=6 | | 7(1-9)=-3(5+3q) |